Prevalence of Chronic Nonspecific Neck Pain Among Office Workers (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: There is a lack of comprehensive research in Lithuania examining the prevalence of chronic nonspecific neck pain among office workers and its impact on daily activities. The aim of this study was to assess the prevalence of chronic nonspecific neck pain among office workers and evaluate its effects on various aspects of daily functioning.Methods: A total of 172 office workers participated in the study by completing a structured questionnaire. The survey collected data on demographic variables (gender, age), duration of sedentary work, presence of neck pain, lower back pain, headaches, use of pain medication, history of neck injuries, as well as the duration and intensity of neck pain. Participants were also asked about the impact of neck pain on personal hygiene, lifting objects, reading, concentration, work performance, driving, sleep, and leisure activities.Results: Of the respondents, 72.4% were women and 27.6% were men, with 95.9% aged between 21 and 65 years. A majority (69.2%) reported working in a sedentary position for more than five years. Neck pain had been experienced at least once in their lifetime by 78% of office workers, and 79.4% had experienced lower back pain. Currently, 7.1% use medication to relieve back pain, while 27.1% reported chronic neck pain lasting longer than three months. According to the Visual Analogue Scale (VAS), 10.8% reported neck pain intensity of 4. At the time of the survey, 27.8% experienced mild neck pain and 11.8% experienced moderate pain. Regarding functional activities, 21.2% performed personal hygiene independently but with mild neck pain; 32.4% experienced mild neck pain when lifting weights; 34.1% while reading; 30.4% while driving. Additionally, 49.4% reported sleep disturbances, and 26% experienced mild neck pain during leisure activities.Conclusion: Chronic nonspecific neck pain is highly prevalent among office workers. Although it does not significantly impair daily functioning for the majority of individuals, mild to moderate pain is frequently reported during various daily activities. Further research will continue to explore the effectiveness of incorporating short breaks during work hours as a potential strategy for managing symptoms and improving musculoskeletal health in this population.